Perancangan Model (Blue Print) Aplikasi Penghitung Sitasi dan ArticleHub Pada Publikasi Jurnal Ilmiah - Yunus, Muhammad; Pratama, Mudafiq Riyan (Puslitbang Sinergis Asa Professional, 2023)
The number of scientific journals, especially in Indonesia, is not commensurate with their quality. This can be seen from the number of journals accredited by SINTA which is not comparable to the number of journals indexed by Garuda. One indicator of a quality journal that is highly useful is the number of citations (scientific impact). In the substantive elements of journal accreditation assessment in Arjuna, the number of citations includes points that have a high score (maximum 8) if those who have cited them over the last 3 years are high (>30 citations). However, to find out the number of citations, the journal must be indexed in dimensions which are crossref products. In accordance with the latest journal accreditation guidelines released in 2021, citations that are recognized only use dimensions. But the problem is that the dimensions calculation process is not real-time, where the citation calculation results will be displayed four times a year. This is certainly not effective considering that scientific articles in journals can be cited by other articles at any time. It is mandatory to use dimensions because currently the Garuda and Sinta portals do not accommodate the needs related to citation calculations. The next problem is that there is no platform in one application that can bring together writers and journal managers, so up to now writers have been looking for just any journal for publication, on the other hand, journal managers have been aggressively promoting through email broadcasts and calls for papers, but sometimes it doesn't feel optimal. So the solution to this problem is the need for a multifunctional platform in the form of a scientific journal citation calculation application and article hub. The results of the research are in the form of a blueprint for the application of citation calculations and articlehub in scientific journal publications. Where the blueprint shows that the citation process is real time or up to date so that the latest number of citations in scientific journals can be known. ​